2018
DOI: 10.1155/2018/1027640
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Alloy C‐276 in Supercritical Water

Abstract: e corrosion behavior of Alloy C-276 in high-temperature and high-pressure water at 500°C and 25 MPa, respectively, was investigated by means of mass gain, scanning electron microscopic observation, and X-ray diffraction. e results indicated that the mass gain rate of Alloy C-276 in supercritical water obeys the parabolic law. e oxide scale was formed on Alloy C-276 with a dual-layer structure, mainly consisting of an outer Ni-rich layer and an inner Cr 2 O 3 /NiCr 2 O 4 mixed layer. Tiny microcracks can also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…The formation of these continuously dense oxides could protect the alloy effectively. It was reported that NiO was not as stable as the spinel and chromium oxides [ 2 , 34 ]. Besides, studies showed that element Fe caused solid solution strengthening when added into Ni-based alloy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these continuously dense oxides could protect the alloy effectively. It was reported that NiO was not as stable as the spinel and chromium oxides [ 2 , 34 ]. Besides, studies showed that element Fe caused solid solution strengthening when added into Ni-based alloy.…”
Section: Resultsmentioning
confidence: 99%
“…A scanning electron microscope (XL30-FEG ESEM, FEI, Hillsboro, OR., USA) was applied to observe the morphology evolution of the oxide film. Before SEM observation, the sample surface was coated with a thin Ni layer to avoid the spoliation during sample preparation [ 34 ]. Phase constituents were identified by an X-ray diffractometer (XRD, Rigaku Corporation, Tokyo, Japan) with Cu-K α radiation with a wavelength of 1.5 Å at 40 kV.…”
Section: Methodsmentioning
confidence: 99%
“…They then react with oxygen (see reaction ), high-temperature water, and anions to form oxides and hydroxides, and finally precipitate on the alloy surface. As for Cr, Ni, and Fe, reaction can further be expressed by reactions –. ,, The second stage takes place in some of the reactions among the oxides and hydroxides mentioned. The two reaction stages can be explained by the solid-state growth mechanism and the metal dissolution/oxide precipitation mechanism .…”
Section: Reactions Of Typical Elementsmentioning
confidence: 99%
“…The two reaction stages can be explained by the solid-state growth mechanism and the metal dissolution/oxide precipitation mechanism . In general, the diffusion phenomenon plays an important role in the oxidation process, and the growth rate of oxide film is determined by the diffusion rates of metal ions and O 2– …”
Section: Reactions Of Typical Elementsmentioning
confidence: 99%
“…The oxide film sample was treated by a sensitize solution (10 g/L SnCl 2 and 1 ml/L 37 % HCl) and an activation solution (0.3 g/L PdCl 2 ). 10 The samples were mounted with epoxy resin and polished down to 0.5 μm before the metallurgical examination. The X-ray diffractions were recorded by a D/Max-2550pc diffrac-tometer equipped with a Cu anti-cathode (40 kV±30 mA).…”
Section: Experimental Partmentioning
confidence: 99%